Review on Melanoma Skin Cancer Treatment by Cold Atmospheric Plasma - Abdullah, Zulaika; Zaaba, SK; Mustaffa, MT; Mohamad, CWSR; Mohtar, JA (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Melanoma is known as the most serious type of skin cancer and the risk of melanoma seems to be around people under 40, especially women. Warning signs of skin cancer can help ensure that cancerous changes are discovered and cured before cancer has spread. Melanoma can be cured successfully if it is detected early. In this review, we discussed the causes, risk factors and prevention methods of melanoma skin cancer, which may lead to early detection of melanoma among people. In addition, this review also shows the stages of melanoma and how to treat melanoma skin cancer. We also highlighted the new suggested skin cancer treatment using cold atmospheric plasma.